1999
DOI: 10.1017/s0007114599001683
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bran supplementation does not affect biochemical markers of bone turnover in young adult women with recommended calcium intake

Abstract: We investigated the effect of wheat bran on biochemical indicators of Ca and bone metabolism in nineteen healthy women, aged 25·5 (se 0·9) years. Subjects received six wheat bran biscuits or six white flour biscuits per day for a period of 4 weeks (crossover). Wheat bran consumption increased fibre intake from 17·7 (se 1·3) to 29·6 (se 1·3) g/d (7 d food record) and enhanced P intake from 1225 (se 59) mg/d to 1663 (se 65) mg/d; P < 0·001. Mean daily Ca intake during wheat bran consumption (1110 (se 82) mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Whether this is of physiological significance in terms of bone health has been explored further. Short-term (4 weeks) and longer-term (2 years) studies have demonstrated that wheat bran in the diet had no significant effect on bone turnover markers in young and older women (Zitterman et al 1999; Chen et al 2004). Therefore, despite the negative effects of wheat bran on calcium bioavailability, there is insufficient evidence to suggest that it has any detrimental effect on bone metabolism, causing accelerated bone loss.…”
Section: Phytic Acid and Wheat Branmentioning
confidence: 99%
“…Whether this is of physiological significance in terms of bone health has been explored further. Short-term (4 weeks) and longer-term (2 years) studies have demonstrated that wheat bran in the diet had no significant effect on bone turnover markers in young and older women (Zitterman et al 1999; Chen et al 2004). Therefore, despite the negative effects of wheat bran on calcium bioavailability, there is insufficient evidence to suggest that it has any detrimental effect on bone metabolism, causing accelerated bone loss.…”
Section: Phytic Acid and Wheat Branmentioning
confidence: 99%
“…In a study of 19 healthy young women (mean age: 25.7 ± 3.9 years), Zittermann et al found no difference in serum biomarkers of bone turnover between the high wheat bran fiber (15g/d) and low wheat bran fiber (1g/d) supplementation groups (16) . Similarly, in a study of healthy individuals in southern India, Harinarayan et al found no difference in PTH levels between 205 participants living in rural areas consuming high phytate/calcium diets and 943 participants living in urban areas consuming low phytate/calcium diets, although both groups had low dietary calcium intake and were vitamin D deficient (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the 2005 US Dietary Guidelines recommend that at least half of the recommended 6–11 grain servings/d comprise whole grain foods ( 8 ) . However, one potential concern is whether the phytic acid in the whole grain foods leads to an increased risk of hip fracture by reducing the bioavailability of dietary minerals ( 9 16 ) , in particular, that of co-ingested Ca. Thus, increased whole grain consumption could have an adverse effect on bone metabolism ( 13 ) , potentially increasing the risk of fracture ( 14 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ursächlich ist der Gehalt an Phytinsäure zu betrachten [18]. Jedoch wird bei knochengesunden jungen Frauen der absorptionshemmende Effekt von enteral zugeführten 14 g Weizenkleie durch einen sofortigen Abfall der renalen Kalziumexkretion kompensiert [20]. Die intestinale Absorption von Kalzium kann durch Vitamin D deutlich verbessert werden.…”
unclassified